Essays on beef economics: an updated understanding of cowherd supply response and wholesale meat demand - Oerly, Amber Kate (Kansas State University, 2022)
The beef supply chain in the United States consists of many actors from the farm to retail level; with approximately 730,000 beef farms moving cattle to feedlots to slaughter plants and finally to various wholesale, retail, and export channels (USDA NASS, 2017). Thus, the U.S. beef industry is known to be one of the most complex segments of the agricultural sector. Periods of increased volatility and uncertainty related to economic, environmental, and social factors have further highlighted the dynamic nature of the U.S. beef industry and supply chain. This thesis contains two articles. The first article analyzes cowherd supply response in the United States and 14 major cow-calf states in the country. The second article estimates wholesale beef demand parameters. In Article 1, partial-adjustment supply models are estimated to quantify how changes in feeder cattle prices impact beef cow inventories at state and national levels. In Article 2, seeming unrelated regression (SUR) models are estimated to obtain updated wholesale beef demand elasticities. Both Articles 1 and 2 provide updated research related to two current knowledge gaps in the U.S. beef industry. Findings in both articles support the notion that price sensitivity may be decreasing in the U.S. beef-cattle industry.
Keywords: Beef; Cowherd supply; Wholesale meat demand